KEMAMPUAN MEMBACA SOAL HITUNGAN CERITA MATEMATIKA SISWA KELAS V SEKOLAH DASAR NEGERI 105 PEKANBARU - Siti Rohaniah; Dudung Burhanudin; H. Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to determine the ability to read a story about a matter of mathematics student of elementary school class V 105 Pekanbaru. This research is using quantitative methods. The populations in this research is all students is the fifth grade off primary school 105 Pekanbarutotaling 160 students. The sample in this research are 40 students drawn using simple random sampling technique. The technique collecting data is a test reading a story about a matter of math with 4 option/alternative. Data analysis technique is using statistics. The research concluded that the ability to read a story about a matter of mathematics students public elementary school class V 105 Pekanbaru category is very low with an average value of 42,25.Keywords: the ability to read, a story about a matter of mathematics.